Prevention of Anthracycline-Induced Cardiotoxicity: The Good and Bad of Current and Alternative Therapies - Sangweni, Nonhlakanipho F.; van Vuuren, Derick; Mabasa, Lawrence; Gabuza, Kwazi; Huisamen, Barbara; Naidoo, Sharnay; Barry, Reenen; Johnson, Rabia (Frontiers in Cardiovascular Medicine, 2022)
Doxorubicin (Dox)-induced cardiotoxicity (DIC) remains a serious health burden, especially in developing countries. Unfortunately, the high cost of current preventative strategies has marginalized numerous cancer patients because of socio-economic factors. In addition, the efficacy of these strategies, without reducing the chemotherapeutic properties of Dox, is frequently questioned. These limitations have widened the gap and necessity for alternative medicines, like flavonoids, to be investigated. However, new therapeutics may also present their own shortcomings, ruling out the idea of “natural is safe”. The U.S. Food and Drug Administration (FDA) has stipulated that the concept of drug-safety be considered in all pre-clinical and clinical studies, to explore the pharmacokinetics and potential interactions of the drugs being investigated. As such our studies on flavonoids, as cardio-protectants against DIC, have been centered around cardiac and cancer models, to ensure that the efficacy of Dox is preserved. Our findings thus far suggest that flavonoids of Galenia africana could be suitable candidates for the prevention of DIC. However, this still requires further investigation, which would focus on drug-interactions as well as in vivo experimental models to determine the extent of cardioprotection.